2014
DOI: 10.1055/s-0034-1385466
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Percutaneous Radiofrequency Lesioning When Treating Recalcitrant Plantar Fasciitis: Clinical Results

Abstract: US should be regarded as a useful objective tool to guide RTL and to monitor the effectiveness of treatment. US-guided percutaneous RTL for recalcitrant PF is a minimally invasive treatment option that yields satisfactory results. Therefore, it should at least be considered before using more invasive procedures. Moreover, obesity leads to delayed improvement but does not affect overall outcome after 12 months. Plantar fascial thickness was correlated with VAS and AOFAS scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…1,2,6,7 In addition, structural and biomechanical factors, including pes cavus, pronated foot, and limited plantar flexion range, may cause plantar heel pain. 2,6,7 Approximately 11% to 15% of cases with chronic plantar heel pain require treatment. 15,16 The standard treatment is conservative, 3,11 yielding successful results in 90% to 95% of the cases and proving to be sufficient in many cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,2,6,7 In addition, structural and biomechanical factors, including pes cavus, pronated foot, and limited plantar flexion range, may cause plantar heel pain. 2,6,7 Approximately 11% to 15% of cases with chronic plantar heel pain require treatment. 15,16 The standard treatment is conservative, 3,11 yielding successful results in 90% to 95% of the cases and proving to be sufficient in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to the best of our knowledge, BMI is the only variable associated with the extent of disability in patients with plantar fasciitis. 6,7,26 Few studies demonstrated that BMI values above normal were associated with plantar fasciitis. [27][28][29] In most studies, the patients were overweight.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations